Long non-coding RNA MALAT1 promotes gastric cancer tumorigenicity and metastasis by regulating vasculogenic mimicry and angiogenesis. (1st June 2017) - Li, Yue; Wu, Zhenzhen; Yuan, Jia; Sun, Li; Lin, Li; Huang, Na; Bin, Jianping; Liao, Yulin; Liao, Wangjun
Abstract: MALAT1 is an oncogenic long non-coding RNA that has been found to promote the proliferation of many malignant cell types and non-malignant human umbilical vein endothelial cells (HUVECs). However, the functions of MALAT1 in vasculogenic mimicry (VM) and angiogenesis and the potential mechanisms responsible have not yet been investigated in any malignancy. Here, in situ hybridization and CD31/periodic acid-Schiff double staining of 150 gastric cancer (GC) clinical specimens revealed that MALAT1 expression was tightly associated with densities of VM and endothelial vessels. MALAT1 knockdown markedly reduced GC cell migration, invasion, tumorigenicity, metastasis, and VM, while restricting HUVEC angiogenesis and increasing vascular permeability. Moreover, MALAT1 was found to regulate expression of VE-cadherin, β-catenin, MMPs 2 and 9, MT1-MMP, p-ERK, p-FAK, and p-paxillin, which have been established as classical markers of VM and angiogenesis and components of associated signaling pathways. Consistent with this, the p-ERK inhibitors U0126 and PD98059 both effectively blocked GC cell VM. In conclusion, MALAT1 can promote tumorigenicity and metastasis in GC by facilitating VM and angiogenesis via the VE-cadherin/β-catenin complex and ERK/MMP and FAK/paxillin signaling pathways. Highlights: MALAT1 correlates with human gastric cancer vasculogenic mimicry (VM) density. MALAT1 expression also correlates with endothelial vessel density in this disease. MALAT1 shRNA inhibits VM and angiogenesis in gastric cancer in vitro and in vivo. MALAT1 knockdown increases vascular permeability in vitro. MALAT1 affects VM via the VE-cadherin/β-catenin complex, ERK/MMP, and FAK/paxillin.